2022
DOI: 10.1002/ejic.202200568
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aluminum N,N‐Dialkylcarbamates by Insertion of CO2 into Al−N Bonds

Abstract: Despite decades of research on various carbamates and their important applications, only one aluminum N,N-dialkylcarbamate (ADC) with an aluminum:carbamate ratio of 1 : 3 has been structurally described and comprehensively studied so far, namely tris(diisopropyl)carbamate. The reasons for this situation include problems with the used synthetic routes. The process of CO 2 insertion into AlÀ N bonds of tris(dialkylamido)alanes resolved these difficulties. Using this advantageous synthetic route, the dimethyl and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…On the one hand, aluminum tris(pyrrolidino)carbamate and aluminum tris(piperidino)carbamate can be prepared and purified according to our previous paper. 29 In this case, the ADC is added to the reaction mixture as a white powder. On the other hand, we found that this purification is not necessary, so that the ADC can be prepared in situ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, aluminum tris(pyrrolidino)carbamate and aluminum tris(piperidino)carbamate can be prepared and purified according to our previous paper. 29 In this case, the ADC is added to the reaction mixture as a white powder. On the other hand, we found that this purification is not necessary, so that the ADC can be prepared in situ .…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses and detailed investigations of the two corresponding tris(dialkylamido)alanes (TDAs) and aluminum N , N -dialkylcarbamates (ADCs) were published by us elswhere. 29,56…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations